Performa dan kandungan protein maggot dengan pakan limbah rumah tangga terfermentasi - Nurina Rahmawati; Brillian Desca Dianingtyas (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Feed is crucial in livestock farming. Rising feed prices are a new challenge, and solutions are needed to reduce feed costs by replacing pellets with homemade protein. Black Soldier Fly are recommended protein sources.The purpose of this study was to determine the results of a mixture of rice waste and green vegetable waste on the performance and nutritional content of maggots. The research method used was an experiment or trial in the form of a Completely Randomized Design (CRD) where the treatment given was a combination with different percentages of the BSF living media. The treatment of the maggot growing media was 5 treatments and 3 replications with the treatment arrangement in this study as follows: P1 = 100% Rice Waste, P2 = 75% Rice Waste + 25% Green Vegetable Waste, P3 = 50% Rice Waste + 50% Green Vegetable Waste, P4 = 25% Rice Waste + 75% Green Vegetable Waste and P5 = 100% Green Vegetable Waste. Observed variables: maggot and colony weight, maggot length, maggot protein and fat content. The results showed that feeding fermented household waste did not have a significant effect (P>0.05) in individual weight and maggot length. However, it did significant effect (P<0.05) in colony weight, crude protein, and crude fat content. The best performance and nutrient content was found in treatment P5 (feeding 100% green vegetable waste) with an average colony weight of 1355.67±11.50 g, crude protein content of 34.88% and crude fat content of 30,92%. The conclusion of this study is that fermented household waste feed has no significantly effect on the performance and crude protein content of maggots